Tryptophan overloading activates brain regions involved with cognition, mood and anxiety - SILVA,LUANA C.A. (2017)
ABSTRACT Tryptophan is the only precursor of serotonin and mediates serotonergic activity in the brain. Previous studies have shown that the administration of tryptophan or tryptophan depletion significantly alters cognition, mood and anxiety. Nevertheless, the neurobiological alterations that follow these changes have not yet been fully investigated. The aim of this study was to verify the effects of a tryptophan-enriched diet on immunoreactivity to Fos-protein in the rat brain. Sixteen male Wistar rats were distributed into two groups that either received standard chow diet or a tryptophan-enriched diet for a period of thirty days. On the morning of the 31st day, animals were euthanized and subsequently analyzed for Fos-immunoreactivity (Fos-ir) in the dorsal and median raphe nuclei and in regions that receive serotonin innervation from these two brain areas. Treatment with a tryptophan-enriched diet increased Fos-ir in the prefrontal cortex, nucleus accumbens, paraventricular hypothalamus, arcuate and ventromedial hypothalamus, dorsolateral and dorsomedial periaqueductal grey and dorsal and median raphe nucleus. These observations suggest that the physiological and behavioral alterations that follow the administration of tryptophan are associated with the activation of brain regions that regulate cognition and mood/anxiety-related responses.